1997
DOI: 10.1039/a700258k
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of the oxidation of aromatic C-nitroso compounds by nitrogen dioxide

Abstract: The oxidation of nitrosobenzene by nitrogen dioxide in carbon tetrachloride has been re-examined, the rate of reaction exhibiting first-order dependence upon the concentrations of both nitrosobenzene and nitrogen dioxide, with a reactant stoichiometry of 1 : 1. The rate of reaction is found to be highly sensitive to the presence of trace quantities of water and intensive drying procedures for the solvent have been developed such that the reaction rate could be reduced to a constant level. For nitrosobenzene an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…In our attempts to use nitrogen dioxide as a catalyst in the oxidation of nitrosobenzene to nitrobenzene we found that the above oxidant cannot be used in a catalytic way and that only when · NO 2 or · NO/O 2 was added in a stoichiometric amount or in excess was nitrosobenzene oxidised to nitrobenzene. This is in agreement with the stoichiometry for reaction (1) established by Bonner and Hancock1b and confirmed by Govenlock et al2a according to which the ratio ArNO/ · NO 2 /ArNO 2 was 1:1:1 [Equation (1)]. …”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In our attempts to use nitrogen dioxide as a catalyst in the oxidation of nitrosobenzene to nitrobenzene we found that the above oxidant cannot be used in a catalytic way and that only when · NO 2 or · NO/O 2 was added in a stoichiometric amount or in excess was nitrosobenzene oxidised to nitrobenzene. This is in agreement with the stoichiometry for reaction (1) established by Bonner and Hancock1b and confirmed by Govenlock et al2a according to which the ratio ArNO/ · NO 2 /ArNO 2 was 1:1:1 [Equation (1)]. …”
Section: Discussionsupporting
confidence: 91%
“…Unfortunately, the catalytic action of · NO 2 was not observed and the complete consumption of nitrosobenzene was obtained only when · NO/O 2 (or · NO 2 ) was added stoichiometrically or in excess. A radical addition mechanism for the oxidation of nitrosoarenes by · NO 2 has already been reported and the kinetics of the reaction studied;2a however, some points on the reactivity of nitrosoarenes towards · NO 2 or · NO still need clarification. For example, on the one hand, the ability of nitroso compounds to act as radical trapping agents is well established,4 and on the other hand, the use of these species for trapping · NO and related radicals has not been of particular interest likely due to the occurrence of more complex reactions other than simple radical addition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The desired pure product was obtained in 95% yield (157 mg, 0.95 mmol) as a light yellow solid, mp 123–125 °C (lit. 40 129.5 °C), after filtration through a short plug of silica topped with Celite using CH 2 Cl 2 . 1 H NMR (500 MHz, CDCl 3 ) δ 8.28 (d, J = 8 Hz, 2H), 7.92 (d, J = 8 Hz, 2H), 3.97 (s, 3H).…”
Section: Methodsmentioning
confidence: 99%
“…3 Reaction of anisole in either chloroform or nitromethane at 25°C gave both 2-and 4-nitroanisole. 4 In some of these papers, the initial formation of a nitroso compound, followed by nitrogen dioxide oxidation to the nitro compound, has been proposed and this led us to carry out kinetic studies of such reactions for a number of aromatic 5 and aliphatic 6 nitrosocompounds. Mononitration of acetonitrile solutions of the three dimethoxybenzenes using nitrogen monoxide-molecular dioxygen mixed gas has been reported; 7 under nitrogen dioxide/dinitrogen tetraoxide 1,2-dimethoxybenzene produces 1,2-dimethoxy-4,5-dinitrobenzene in addition to 1,2dimethoxy-4-nitrobenzene.…”
mentioning
confidence: 99%